Assessing the effectiveness of landscape-scale forest adaptation actions to improve resilience under projected climate change - Maxwell, Charles J.; Scheller, Robert M.; Wilson, Kristen N.; Manley, Patricia N. (Frontiers in Forests and Global Change, 2022)
Climate change will increase disturbance pressures on forested ecosystems worldwide. In many areas, longer, hotter summers will lead to more wildfire and more insect activity which will substantially increase overall forest mortality. Forest treatments reduce tree density and fuel loads, which in turn reduces fire and insect severity, but implementation has been limited compared to the area needing treatment. Ensuring that forests remain near their reference conditions will require a significant increase in the pace and scale of forest management. In order to assess what pace and scale may be required for a landscape at risk, we simulated forest and disturbance dynamics for the central Sierra Nevada, USA. Our modeling framework included forest growth and succession, wildfire, insect mortality and locally relevant management actions. Our simulations accounted for climate change (five unique global change models on a business-as-usual emissions pathway) and a wide range of plausible forest management scenarios (six total, ranging from less than 1% of area receiving management treatments per year to 6% per year). The climate projections we considered all led to an increasing climatic water deficit, which in turn led to widespread insect caused mortality across the landscape. The level of insect mortality limited the amount of carbon stored and sequestered while leading to significant composition changes, however, only one climate change projection resulted in increased fire over contemporary conditions. While increased pace and scale of treatments led to offsets in fire related tree mortality, managing towards historic reference conditions was not sufficient to reduce insect-caused forest mortality. As such, new management intensities and other adaptation actions may be necessary to maintain forest resilience under an uncertain future climate.